THE INFLUENCE OF RELIGIOSITY AND PERCEPTIONS OF INTERNAL CONTROL ON BAD DEBTS OF REVOLVING FUNDS IN PROGRAM KOTA TANPA KUMUH (KOTAKU) IN JAMBI CITY - Indah Dwi Lestari; Tarmizi; G.W.I. Awal Habibah (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2023)
This study aims to analyze the effect of religiosity and internal control on bad credit of revolving funds in the City Without Slums Program (KOTAKU) in Kasang Jaya Village, Jambi City. The research method uses quantitative with a survey using a questionnaire distributed to KOTAKU program participants and related parties in the kelurahan. The results showed that the level of religiosity of respondents had a positive and significant influence on the level of religiosity in the implementation of the KOTAKU program. Respondents who have a high level of religiosity tend to be more honest and have integrity in using the revolving fund program. In addition, it was also found that a good level of internal control in the management of revolving funds has a positive and significant influence on bad credit in the KOTAKU program..